A research on the technology transfer models between universities, research institutes, and companies: suggest recommendation - Le Minh Hai; Chu Van Tung; Nguyen Phuong Tuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
In the knowledge-based economy, building and strengthening relationships between research institutes, universities and companies plays an extremely essential role in socio-economic development. This relationship is aimed to support each other for the mutual interest of all parties involved in. These cooperation activities are diverse, including knowledge and technology transfer (KTT) from universities, research institutes to companies. There have been many models of cooperation between each party introduced. However, each model depends on different characteristics among countries such as the United States, Mexico, etc. Some new trends in technology transfer have appeared more recently, such as technology transfer (technology transfer) through spin-off, startup companies, open innovation or collaborative research. In Vietnam, the technology transfer model through Technology transfer office, or centers is gradually being built. However, in the 4.0 era, the development of technology transfer models in Vietnam should be combined and connected with a well-invested and developed information technology platform. In addition, it is important to note that it is necessary to remove barriers to promote technology transfer through the formation of spin-off companies. Code: 22121201